Negotiating Species-Based Identity: Cultural Hybridity in Paru Itagaki’s Beastars - Ashardian Indra Rismanto; Rizal Octofianto Datau (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2026)
This article examines Paru Itagaki’s manga series Beastars through Bhabha’s (1994) postcolonial perspective. Utilizing Bhabha’s (1994) concepts of hybridity, ambivalence, mimicry, and the Third Space of Enunciation, the study analyses the narrative and its visual elements. Close readings of panel composition, character archetypes, and visual reversals show how Beastars exposes the fragility of species-based cultural classifications and the psychic disorientation that follows when familiar categories collapse. The series initially presents carnivores and herbivores as two opposing groups, then unsettles this division through the actions of Louis and Legoshi. Louis, an herbivore who adopts carnivore-like authority, and Legoshi, a carnivore who uses his strength to protect herbivores, disrupt the meanings attached to their species. Both characters expose these boundaries as constructed categories that remain open to continual revision. Through them, Beastars shows how identity can emerge from unstable positions between established categories. The study argues that Beastars critiques species-based essentialism while illustrating the productive function of the Third Space, suggesting that cultural transformation arises through the hybrid subject’s ability to unsettle authority and create new ways of being. Beastars thus presents Bhabha’s (1994) ever-hybrid “international culture” as a site of ongoing negotiation rather than fixed identity.